Alloying strategies for additive manufacturing of Ti6Al4V based alloys, composites and functionally graded materials: Microstructure and phase evolution of intra and inter-layer - Yilei Shi; Shuili Gong; Haiying Xu; Zhuang Wang; Guang Yang; Bojin Qi (Journal of Materials Research and Technology, 2023)
The further developments of additive manufacturing (AM) provides a possibility for Ti6Al4V and its functionally graded materials (FGMs), but limits further applications due to its low ductility, low microhardness and poor wear resistance. The key lies in the presence of microstructures such as epitaxial columnar β-grain orientation and heterogeneous phase distribution in AM Ti6Al4V, as well as the interfacial bonding problems (intermetallic phases, delamination, cracking) in AM Ti6Al4V FGMs. In order to address these fundamental intra and inter-layer problems, firstly the microstructure and phase evolution process of AM Ti6Al4V columnar-to-equiaxed transformation (CET) promoted by some alloying strategies was summarized in this paper according to alloying elements and reinforcing particle types. Subsequently, controlled changes in the composition and microstructure of AM Ti6Al4V FGMs were achieved by adding interlayers/introducing gradient interfaces, and the metallurgical reactions and phase transformation mechanisms that inhibit the formation of intermetallic compounds and interfacial defects were explored. Finally, the difficulties and future research directions for alloying strategies to achieve high strength and ductility of AM Ti6Al4V were presented. This review aims to improve the reliability of AM Ti6Al4V and its FGMs for applications in critical load-bearing structures through in-situ alloying and multi-material for the microstructure design of AM Ti6Al4V.